Predictability of kinetic estimated glomerular filtration rate for acute kidney injury in patients undergoing coronary artery bypass surgery - Mohammad Ali Haghighatpanah; Sadegh Mazaheri-Tehrani; Amirhosein Adibzadeh; Negar Ostadsharif; Parham Moradi; Mahshad Vali; Roya Riahi; Mohsen Mirmohammadsadeghi (BMC Nephrology)
Abstract Background Acute kidney injury (AKI) is a serious complication of coronary artery bypass grafting (CABG). This study aimed to assess the efficacy of kinetic estimated glomerular filtration rate (KeGFR) in predicting AKI in patients undergoing CABG. Additionally, we sought to identify potential factors contributing to the occurrence of AKI. Methods This retrospective cohort study was conducted at Shahid Chamran Specialty Heart Hospital in Isfahan, Iran, among patients undergoing CABG between November 2018 and May 2021. The baseline eGFR of the patients was calculated using the Modification of Diet in Renal Disease (MDRD) formula. Postoperatively, renal function was assessed using the KeGFR equation. The percentage decrease in KeGFR after surgery compared to baseline eGFR was utilized to evaluate its predictive ability for AKI incidence during hospitalization. According to KDIGO criteria, participants were divided into AKI and non-AKI groups. Results Among 558 included individuals (81.2% male), 186 patients (33.3%) were diagnosed with AKI during hospitalization. Patients with AKI were older and had more comorbidities like hypertension, heart failure, and anemia compared to those without AKI. Additionally, AKI cases exhibited higher rates of blood product transfusions, longer intubation periods, and extended intensive care unit (ICU) stays. The percentage decrease in KeGFR from baseline demonstrated acceptable accuracy in predicting AKI cases (AUC (95%CI): 0.808 (0.753 to 0.864)). Risk factors for AKI in our population included age over 65, smoking, and prolonged intubation time. We found that patients with higher values of neutrophil-lymphocyte-platelet ratio (NLPR) had an increased risk of developing AKI compared to those with lower values (OR: 1.74; 95%CI: 1.07 to 2.83). Conclusion KeGFR demonstrated desirable predictive accuracy for AKI incidence following CABG. Meanwhile, NLPR emerged as a new clinically useful biomarker for monitoring renal function post-CABG. Further prospective investigations are recommended in different settings and other cardiac operations. Trial registration Clinical trial number not applicable.